UPAYA PENINGKATAN JEJARING UMK KECAMATAN CUGENANG MELALUI PENDIRIAN ASOSIASI PENGUSAHA CUGENANG - Muhammad Setiawan Kusmulyono; Alvita Fiorentina, Chaya Adzan Hartanta, Klaudia Katerina, Livia Wilianggi, Metta Ciu Listiyani, Rai (KUAT : Keuangan Umum dan Akuntansi Terapan, 2020)
The challenges of developing Micro, Small and Medium Enterprises in Cugenang Subdistrict, Cianjur Regency are very diverse. One of the toughest challenges is the existence of internal competition that arises between SME entrepreneurs in the Cugenang District itself. It is occured because there is no clear communication network to manage the distribution of MSMEs in Cugenang District. It impacted internal competition between MSME, product quality problems, the competence of MSME entrepreneurs, and uneven product distribution. The student group that became the initiator of Prasetiya Mulya Community Development as community service activities identified problems through interviews, direct discussions, and 1-month observations. One of the positive results obtained is the desire of MSME entrepreneurs to cooperate and network in marketing their products. Unfortunately, this desire does not yet have a clear framework for the activities. Therefore, a group of students with MSME entrepreneurs took the initiative to gather these entrepreneurs in a simple forum which later became the pilot of the Cugenang Entrepreneurs Association (APC) organization. APC was officially established on February 2, 2019 and is currently able to reach the minimum target to become a communication forum for MSME entrepreneurs Cugenang in marketing its products out of the Cugenang Sub-District area and improving the quality of local MSME products.